2004
DOI: 10.1074/jbc.m409942200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of Repair Mechanism of DNA Photolyase by FAD-induced Paramagnetic Relaxation Enhancement

Abstract: Cyclobutane pyrimidine dimer (CPD) photolyases, which contain FAD as a cofactor, use light to repair CPDs. We performed structural analyses of the catalytic site of the Thermus thermophilus CPD photolyase-DNA complex, using FAD-induced paramagnetic relaxation enhancement (PRE). The distances between the tryptophan residues and the FAD calculated from the PRE agree well with those observed in the x-ray structure (with an error of <3 Å). Subsequently, a single-stranded DNA containing 13 C-labeled CPD was prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…PRE analysis for such systems is simple, since there are no pseudo-contact shifts, and Curie-spin relaxation that could potentially exhibit significant cross-correlation with other relaxation mechanisms (2,3), is negligible. Using this type of PRE data, macromolecular structures have been characterized for soluble proteins (4-10), protein-protein complexes (11)(12)(13)(14), protein-oligosaccharide complexes (15,16), protein-nucleic acid complexes (17)(18)(19)(20)(21), and membrane proteins (22,23). The PRE can also provide information relating to large-scale dynamics that accompany changes of paramagnetic center -1 H distances, for example in non-specific protein-DNA interactions (24,25) and interdomain motions (26).…”
Section: Introductionmentioning
confidence: 99%
“…PRE analysis for such systems is simple, since there are no pseudo-contact shifts, and Curie-spin relaxation that could potentially exhibit significant cross-correlation with other relaxation mechanisms (2,3), is negligible. Using this type of PRE data, macromolecular structures have been characterized for soluble proteins (4-10), protein-protein complexes (11)(12)(13)(14), protein-oligosaccharide complexes (15,16), protein-nucleic acid complexes (17)(18)(19)(20)(21), and membrane proteins (22,23). The PRE can also provide information relating to large-scale dynamics that accompany changes of paramagnetic center -1 H distances, for example in non-specific protein-DNA interactions (24,25) and interdomain motions (26).…”
Section: Introductionmentioning
confidence: 99%
“…They are activated by blue light and contain FAD as the catalytic chromophore and either methenyltetrahydrofolate (MTHF) or 8-hydroxy-7,8-didemethyl-5-deazariboflavin (8-HDF) as the second chromophore (Sancar 1994(Sancar , 2003. During last 1 3 few years, additional antenna cofactors such as FMN, FAD and 6,7-dimethyl-8-ribityl-lumazine have been identified in photolayses (Geisselbrecht et al 2012;Klar et al 2006;Ueda et al 2004). …”
Section: Plant-like Cryptochromesmentioning
confidence: 99%
“…2, trace 4), suggesting that the enzyme was in the FADH ⅐ form. NMR spectra of the enzyme with FADH ⅐ , in which the resonances from the atoms nearby FADH ⅐ had disappeared because of the FAD-induced paramagnetic relaxation enhancement (17), also suggested that Ͼ90% of the enzyme was in the FADH ⅐ form. However, the absorbance around 450 nm was also partially regenerated.…”
Section: Development Of a Purification Protocol Designed To Retain Thmentioning
confidence: 99%
“…These structures share a similar overall fold consisting of an ␣/␤ domain and a helical domain. Our previous NMR analysis revealed that the CPD is bound to a FAD-containing cavity in the helical domain (17,18). The crystal structures of the CPD photolyases from E. coli and A. nidulans contain MTHF and 8-HDF, respectively, in the ␣/␤ domain (12,13,15,16), and the second chromophores are ϳ15 Å away from the FAD.…”
mentioning
confidence: 99%